1984
DOI: 10.1002/eji.1830140916
|View full text |Cite
|
Sign up to set email alerts
|

The origin of follicular dendritic cells in the mouse and the mechanism of trapping of immune complexes on them

Abstract: F1----parental bone marrow chimeras between CBA and B10 mice were used to show that even after 1 year follicular dendritic cells (FDC), also termed dendritic reticular cells, are not derived from bone marrow stem cells. However clusters of cells wrapped in the dendritic processes of FDC, isolated by enzyme digestion of the spleen contain B cells originating from donor marrow. This implies that evidence for the presence of antigens such as Ia-like detected by others (Gerdes, J. and Stein, H., Clin. Exp. Immunol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
68
0

Year Published

1994
1994
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 144 publications
(74 citation statements)
references
References 12 publications
6
68
0
Order By: Relevance
“…Kapasi et al (23) reported that precursors of FDC exist in bone marrow, move into target organs, and differentiate into FDC, while Humphery et al (24) and Yamakawa et al (25) did not support the idea that FDC originate from bone marrow. According to previous reports using knockout mice, lymphotoxin-␣ and TNFRI play a crucial role in establishing FDC in vivo (26 -30).…”
Section: Discussionmentioning
confidence: 99%
“…Kapasi et al (23) reported that precursors of FDC exist in bone marrow, move into target organs, and differentiate into FDC, while Humphery et al (24) and Yamakawa et al (25) did not support the idea that FDC originate from bone marrow. According to previous reports using knockout mice, lymphotoxin-␣ and TNFRI play a crucial role in establishing FDC in vivo (26 -30).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the ultrastructure, cytology, and immunophenotype of FDCs do not support a hematopoietic origin but favor a mesenchymal origin and raise the issue whether they arise from further differentiation of a local fibroblastic reticular cell [7][8][9] or from a migratory mesenchymal cell, likely from the bone marrow [10,11]. Most ultrastructural studies point to a fibroblastic origin for FDCs in their less differentiated forms; however, the mature FDCs differ from fibroblasts in that they bear a complex network of long branching dendrites that retain an electron-dense material and possess desmosomal and adherent junctions [5].…”
Section: Origin Of Fdcsmentioning
confidence: 99%
“…There exists good evidence that B cell memory requires continuous restimulation by antigen, which is facilitated by follicular dendritic ceils (24,25) presenting the trapped B cell epitope in its original immunogenic form. T cells, however, recognize epitopes consisting of MHC molecules plus processed antigen.…”
Section: And D) Effector Cells Were Assayed 3 (A and B) Or 6 (B And mentioning
confidence: 99%